Domestic military missions in Latin America: Civil-military relations and the perpetuation of democratic deficits. (15th February 2022) - Jenne, Nicole; Martínez, Rafael
Abstract: Latin American militaries are today in many regards inoperative and obsolete as an instrument of defence. Yet, they seek to maintain their organisational power and privileges. Governments, on the other hand, lack the adequate means to fight criminality, persisting poverty and social inequality. In an apparent win-win situation, Latin American governments have used the military as a wildcard to step in where civilian state capacity falls short, including for urban and border patrols, literacy campaigns and to collect garbage, among many other tasks. The military's manifold internal use has been defended mainly based on pragmatic reasons. We argue instead that the ostensive pareto optimality between militaries and governments has had negative effects for civil-military relations from a democratic governance point of view that takes into consideration the efficiency and effectiveness of how the state delivers basic services across different policy areas.